YURIY YU. KOSTYUK (KOSTYO) (1912–1998): MILESTONES OF LIFE AND WORK - Іvan Pylypets (Культура і мистецтво у сучасному світі)
The article is dedicated to life and career of the outstanding music artist Ukrainian Transcarpathia and Eastern Europe Y.Y. Kostyuk (Kosto).